Sampling and Compilation Method of Load Spectrum of Passenger Car Transmission - Chen Dexin; Li Songsong; Shi Xinglei (Jixie chuandong)
To study the sampling and compilation method of load spectrum of passenger car transmission,taking a certain type of front-engine,front-wheel-drive passenger car transmission as an example,according to different road conditions,the road random load of this passenger car transmission is collected.According to the characteristics of the load,the amplitude cycle counting method is employed to complete the statistical treatment for various time dependent loads tested in the road test.The design load spectrum of the passenger car transmission is compiled.The sampling and compilation method of load spectrum of the passenger car transmission is established.The method can provide accurate design input conditions for passenger car transmission,and provide a reference for accurate fatigue life prediction and fatigue test.